A Review on Augmented Reality and YOLO - Uma, M.; Abirami, S.; Ambika, M.; Kavitha, M.; Sureshkumar, S; R, Kaviyaraj (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
This study comprehensively examines two emerging technologies, Augmented Reality(AR) and You Only Look Once (YOLO): these two technologies revolutionized object detection and computer vision. YOLO instantly identifies objects in images and videos, whereas AR superimposes virtual objects in the real world. This review integrates AR and YOLO and covers the aspects of each, its applications, drawbacks, and future directions. Also, this article explores the fundamentals of augmented reality and several types of AR systems, including marker-based, marker-less, and projection-based systems. The review explains how YOLO works with single network architecture and real-time detection from YOLOv1 through YOLOv8. Finally, this study summarizes the key takeaways from YOLO's development and offers insights into its future, outlining potential research directions to enhance real-time object detection systems further. Furthermore, the study highlights the potential of integrating YOLO and AR to improve user interactions. It also addresses the challenges associated with integrating AR and YOLO, providing a comprehensive overview of the obstacles that must be overcome.